ALÇAK GERİLİM DAĞITIM ŞEBEKELERİNDE NÖTR KOPUKLUĞUNUN ALGILANARAK TEÇHİZATIN KORUNMASI - İŞİVAR, MURAT (Fırat Üniveristesi, 2025)
Alçak Gerilim Dağıtım şebekelerinde nötr hattının kopması sistemde gerilim dalgalanmalarına, cihazlarda aşırı gerilimler oluşmasına ve hasarlanmalara, hatta yangınlara sebebiyet verebilmektedir. Nötr hattının koptuğu yer ve bu yerin tüketiciye olan mesafesi de bu etkide önemli bir unsurdur. Bu durumun önüne geçebilmek için nötr iletkeninin belirli periyotlar ile kontrol edilmesi, yedek nötr iletkeninin bulundurulması, topraklama sisteminin düzenli olarak kontrol edilmesi ve koruma ekipmanlarının kullanılması gibi tedbirlerin uygulanması gerekmektedir. Günümüzde dağıtım şebekelerinde birçok koruma elemanı kullanılmakla birlikte, AG Dağıtım Şebekelerinde nötr kopmasında teçhizatı koruyabilecek sınırlı sayıda koruma ekipmanı bulunmaktadır. Bu tez çalışmasında; Öncelikle örnek bir AG dağıtım şebekesi Matlab Simulink programında simüle edilerek, dağıtım şebekesinde meydana gelen bir nötr kopmasının Dağıtım Şebekesi üzerindeki tüketicilere etkileri analiz edilecektir. Daha sonra, nötr kopmasını algılayan mikroişlemci tabanlı bir sistem tasarlanıp, dağıtım şebekesi üzerinde meydana gelecek bir nötr kopması durumunda oluşacak aşırı gerilimlere karşı teçhizatın korunması deneysel olarak gerçekleştirilecektir. Çalışmanın temel amacı, yapılacak algılayıcı sistem ile nötr kopma arızası durumunda insan hayatını korumak ve ayrıca tüketicilere ait cihazlar ile dağıtım şebekesindeki teçhizatın zarar görmesinin önüne geçmektir.

Detecting neutral disconnection in Low Voltage Distribution Networks and consequently protecting the equipment is of vital importance in electrical energy systems. Neutral line disconnection is a critical issue that often goes unnoticed but poses threats such as equipment malfunctions, device burnouts, and risks to human safety. The continuous and safe use of electrical energy is one of the fundamental requirements of modern life. Therefore, the early detection and intervention of this issue are crucial not only for individual users but also for industrial facilities and public services. This topic requires the integration of theoretical knowledge with practical applications, embodying a multi-faceted structure. Early detection of neutral disconnection necessitates the integrated operation of sensor systems, data processing algorithms, and decision-making mechanisms. This requires a complex engineering process that incorporates both hardware and software components. During system design, the accurate determination of sensor calibrations, error tolerances, and reliability metrics is of utmost importance. In particular, measuring the imbalance between different phases and correctly classifying the causes of these imbalances pose a significant challenge in identifying the source of the problem. The primary motivation for this seminar is to ensure the protection of electrical equipment and the safety of users. The repair of electrical damages is often costly and time-consuming. Moreover, power outages can cause significant financial losses in industrial production. Therefore, the early detection of neutral disconnection will reduce economic damage, ensure business continuity, and extend the lifespan of electrical devices. This study has been carried out to contribute to making the electrical infrastructure safer and more efficient.
Protection of equipment by detecting neutral disconnection in low voltage distribution networks
Keywords: Elektrik ve Elektronik Mühendisliği